Mono or double Pd-catalyzed C–H bond functionalization for the annulative π-extension of 1,8-dibromonaphthalene: a one pot access to fluoranthene derivatives - Nahed Ketata; Linhao Liu; Ridha Ben Salem; Henri Doucet (Beilstein Journal of Organic Chemistry, 2024)
The Pd-catalyzed annulative π-extension of 1,8-dibromonaphthalene for the preparation of fluoranthenes in a single operation has been investigated. With specific arenes such as fluorobenzenes, the Pd-catalyzed double functionalization of C–H bonds yields the desired fluoranthenes. The reaction proceeds via a palladium-catalyzed direct intermolecular arylation, followed by a direct intramolecular arylation step. As the C–H bond activation of several benzene derivatives remains very challenging, the preparation of fluoranthenes from 1,8-dibromonaphthalene via Suzuki coupling followed by intramolecular C–H activation has also been investigated to provide a complementary method. Using the most appropriate synthetic route and substrates, it is possible to introduce the desired functional groups at positions 7–10 on fluoranthenes.